If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying B + -9 + 6b = 40 Reorder the terms: -9 + B + 6b = 40 Solving -9 + B + 6b = 40 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '9' to each side of the equation. -9 + B + 9 + 6b = 40 + 9 Reorder the terms: -9 + 9 + B + 6b = 40 + 9 Combine like terms: -9 + 9 = 0 0 + B + 6b = 40 + 9 B + 6b = 40 + 9 Combine like terms: 40 + 9 = 49 B + 6b = 49 Add '-6b' to each side of the equation. B + 6b + -6b = 49 + -6b Combine like terms: 6b + -6b = 0 B + 0 = 49 + -6b B = 49 + -6b Simplifying B = 49 + -6b
| 380=40t+60t-120 | | 2x+-5x+(8x+6x)=5 | | 2x-5x+(8x+6x)=x | | a=p+1fora | | -208=4x+7(-6x-8) | | -208=4c+7(-6x-8) | | -10-5v+1+8v=7+7v | | 12xy=24 | | a^3x-b^3=0 | | (1+i)z-2i=4z+1 | | 5(a-4)-(8a)=55 | | -2+4y=19 | | -15-10x=4-3(-2-5x) | | 11-3y=1 | | 3x^2-5x+4+x^2= | | -5+4y=19 | | 1+4x-x=x-5 | | P=4w-8 | | 3/4k-10=1 | | -18=n-4n | | 3.2=-3.8-7 | | -18=2-4n | | 4(2.4x-1.6)-8.6x=-8.3 | | 2x(2y+3)-(2y+3)=7 | | 0=-16x^2-16x+5 | | -9*-2-3y=6 | | 9-3f=60 | | 5h+2(h-11)=-5 | | 7x=8x+-4 | | y=-16x^2-16x+5 | | 3x+12x-7=5x+3 | | X+19x=180 |